APLIKASI VARIASI SUKROSA DAN PERBANDINGAN GELATIN-KARAGENAN PADA PERMEN JELI KOPI ROBUSTA (Coffea canephora P.) - Septy Handayani; Triana Lindriati; Fuji Kurniawati; Puspita Sari (JURNAL AGROTEKNOLOGI, 2021)
Robusta coffee is widely cultivated in Indonesia, and it is often processed into ground coffee. In this study, coffee jelly candy was made for product diversification of coffee. In this case, gel forming agents and sugar are needed to build jelly candy texture, aroma, and taste. The aim of this research was to study the characteristics of coffee jelly candy as affected by sucrose concentration and the ratio of carrageenan to gelatin. A completely randomized design using two factors (sucrose concentration of 40% and 60%; and gelatin to carrageenan ratio of 25:75, 50:50, and 75:25 w/w) was employed. The result showed that sucrose concentrations and gelatin to carrageenan ratio significantly (α > 5%) affected texture, color, moisture content, ash content, and organoleptic parameters (preference towards color, texture, taste, and overall). However, sucrose concentration and the ratio of gelatin to carrageenan not significantly (α < 0,05%) affect antioxidant activity and polyphenol concentration. The effectiveness test showed that coffee jelly candy with 40% sucrose concentration and the ratio of gelatin:carrageenan 50:50 had the highest score with L (lightness) value of 46.79, hardness of 54.53 g/mm, moisture content of 19.26%, ash content of 1.36%, antioxidant activity of 26.63%, total polyphenol of 0.46 mg GAE/mL, preference towards color of 5.60 (rather like), preferences towards aroma of 5.83 (rather like), preferences towards taste of 5.10 (rather like), preferences towards texture of 5.13 (rather like), and overall preference of 5.57 (rather like). Keywords: carrageenan, gelatin, jelly candy, organoleptic, robusta, sucrose